Analysis of stomach contents in green back mullet, Chelon subviridis from Merbok Estuary, Malaysia - Fatema, Kaniz; Omar, Wan Maznah Wan; Isa, Mansor Mat (Bangladesh Journal of Zoology, 2015)
Abstract not available Bangladesh J. Zool. 43(1): 153-156, 2015